2020
DOI: 10.1101/2020.09.18.20196451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple measures of depression to enhance validity of Major Depressive Disorder in the UK Biobank

Abstract: Background: The UK Biobank (UKB) contains data with varying degrees of reliability and completeness for assessing depression. A third of participants completed a Mental Health Questionnaire (MHQ) containing the gold-standard Composite International Diagnostic Interview (CIDI) criteria for assessing mental health disorders. Aims: To investigate whether multiple observations of depression from sources other than the MHQ can enhance the validity of Major Depressive Disorder. Methods: In participants who did … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Our results suggest that single-item diagnoses may be sufficient for discovery of shared genetic effects, but investigation of disorder-specific factors or outcomes would require an algorithm-based or other strictly-defined measure. In designing future studies, including and combining multiple methods of ascertaining diagnostic status, such as single-item, algorithm-based, and EHR data, may yield more robust phenotypes and increase power for analyses (21).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggest that single-item diagnoses may be sufficient for discovery of shared genetic effects, but investigation of disorder-specific factors or outcomes would require an algorithm-based or other strictly-defined measure. In designing future studies, including and combining multiple methods of ascertaining diagnostic status, such as single-item, algorithm-based, and EHR data, may yield more robust phenotypes and increase power for analyses (21).…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers have argued that broad depression phenotyping shows the same genetic overlap with neuroticism and therefore is not specific to MDD (8). Algorithm-based MDD has also been found to have significantly higher heritability than single-item MDD, suggesting that utilising the single-item measure could decrease the power to detect genetic effects despite the increase in sample size (8,21). These reduced heritability estimates could be partially explained by the low sensitivity of single-item for algorithm-based MDD and any anxiety, as misclassification dilutes the power of case-control analyses to detect differences between the samples (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We created two depression case groups: strictly-defined cases termed ‘stringent depression’ and liberally-defined cases termed ‘any depression’. We have previously shown that SNP-based heritability increases with multiple endorsements of depression 16 . We therefore classified ‘stringent depression’ as participants endorsing at least three of the following depression measures: ICD-10 diagnoses (F32-F33.9); self-reported depression; self-reported antidepressant usage; single or recurrent depression (defined by Smith, et al 17 from responses to a touchscreen questionnaire completed at baseline by 172,751 participants); or answered ‘yes’ to the touchscreen questionnaire: “Have you ever seen a GP/psychiatrist for nerves, anxiety, tension or depression?”.…”
Section: Methodsmentioning
confidence: 96%
“…Detail on the derivation of each indication of depression, schizophrenia and bipolar can be found in Supplementary Materials from our previous publication 16 .…”
Section: Methodsmentioning
confidence: 99%